USING THE ABILITY OF THE E- MANAGEMENT STRATEGY TO BUILD STRATEGIES TO ADDRESS JOB BURNOUT IN EDUCATIONAL INSTITUTIONS: AN APPLIED STUDY ON A SAMPLE OF ADMINISTRATIVE STAFF WORKING AT BABYLON UNIVERSITY - Mawed Kadhim Jaber (American Journals, 2024)
E- management strategies are at the heart of the technological developments that have conquered the modern world, because it has become a necessity for organizations and institutions to evolve and keep up with the changes in today's work environment, and because their application reflects the manifestation of this willingness in organizations and institutions across the board. Contributions to aspects, including its direct contribution to reducing or reducing the level of work fatigue and finding effective solutions and properly solving these problems. Therefore, the problem to be addressed in this study is identified and represented by the following question: To what extent does this strategy (e-management) contribute to reducing burnout at work and to what extent can appropriate strategies be found to deal with it? The researcher aimed to use questionnaires as the main data collection tool for research samples, and randomly selected (45) administrative employees of different ranks, of whom 39 were recovered for analysis, with a response rate of (68%) . This study used statistical methods based on the SPSS program for data processing and analysis. The main conclusion is that electronic management strategy is a new management method that has brought profound changes to the management environment of various social organizations. One of its advantages is that it provides the best services to the beneficiaries and better performance to employees and workers.
Keywords: E- management, burnout, building strategies.